الفلسفة الماركسية وموقف مفكري المسلمين منها:دراسة تحليلية نقدية: Marxist Philosophy and Islam's Stance on It: A Critical-Analytical Study - Zarkasyi, Amal Fathullah; Muhammad, Allan; Aidil Putra Syurbakti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This research aims to study Marxism as a philosophical and social movement that emerged in the 19th century in response to the economic and social transformations brought about by the Industrial Revolution, and to analyze its theoretical structure in light of its central concepts such as dialectical materialism, historical materialism, and class struggle. The researcher adopted a comparative analytical approach, through a critical reading of classical Marxist texts and comparing them with Islamic intellectual positions, to reveal the strengths and weaknesses of the Marxist interpretation of man and society. The results showed that Marxism has made an important contribution to the analysis of economic injustice and the critique of capitalism through the concept of the exploitation of the working class and the accumulation of capital. However, it remains limited because it interprets history from a purely materialistic perspective and neglects the spiritual and metaphysical dimensions of human existence. The research also showed that Islamic thought, on the other hand, offers an integrative vision that reconciles the material and the spiritual, restoring social justice to its ethical and spiritual dimension. The scientific importance of this research lies in its contribution to renewing the dialogue between Marxist and Islamic thought and highlighting the need to develop an alternative epistemological model that balances economic analysis and human values, in line with contemporary challenges such as globalization, environmental crises, and digital transformations.